Investigation of Solar and Solar-Gas Thermal Energy Sources - Ivan Herec; Jan Zupa (Advances in Electrical and Electronic Engineering, 2003)
The article deals with the investigation of solar thermal sources of electrical and heat energy as well as the investigation of hybrid solar-gas thermal sources of electrical and heat energy (so called photothermal sources). Photothermal sources presented here utilize computer-controlled injection of the conversion fluid into special capillary porous substance that is adjusted to direct temperature treatment by the concentrated thermal radiation absorption.